2016
DOI: 10.1007/s11295-016-1027-6
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of reproductive phenology traits and related QTL identification in apricot

Abstract: Reproductive phenological traits of great agronomical interest in apricot species, including flowering date, ripening date and fruit development period, were studied during 3 years in two F 1 progenies derived from the crosses 'Bergeron' × 'Currot' (B × C) and 'Goldrich' × 'Currot' (G × C). Results showed great variability and segregation in each population, confirming the polygenic nature and quantitative inheritance of all the studied traits. Genetic linkage maps were constructed combining SSR and SNP marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 65 publications
5
29
0
Order By: Relevance
“…The high positive correlation between MD and FD time, observed herein for the first time in sweet cherry, has been previously observed in peach and apricot 4,5,27 . The results indicate that MD is highly dependent on FD time in sweet cherry, as has been previously observed in other Prunus species.…”
Section: Haplotype Analysis Of Lg4supporting
confidence: 83%
See 2 more Smart Citations
“…The high positive correlation between MD and FD time, observed herein for the first time in sweet cherry, has been previously observed in peach and apricot 4,5,27 . The results indicate that MD is highly dependent on FD time in sweet cherry, as has been previously observed in other Prunus species.…”
Section: Haplotype Analysis Of Lg4supporting
confidence: 83%
“…FD time has also been investigated in Prunus, but only in apricot and peach. A main QTL for FD time was found on the same LG4 genomic region where the MD QTL has been identified in these species 5,13,14 . In this region, NAC transcription factors have been reported as candidate genes for MD in peach 15 and other Rosaceae species like apple 16 .…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…However in our work, this QTL explained a smaller part of the variation (6.0%) ( Table 1) and was not detected all years. Several works indicated that the LG4 QTL had a larger effect on BT of high chill cultivars (Castède et al, 2014;Kitamura et al, 2018), while in low chill cultivars, as in this work, the variation in BT is more dependent in the QTL on LG1 (Fan et al, 2010;Sánchez-Pérez et al, 2012;Zhebentyayeva et al, 2014;Salazar et al, 2016). LG1 candidate genes (DAM1-6) are related to CR, and therefore these genes may have a larger contribution to BT of low chilling cultivars.…”
Section: Other Minor Qtlssupporting
confidence: 52%
“…In sweet cherry, skewed segregation in F 1 populations towards high CR, but not late bloom, was also observed (Castède et al, 2014). This was also the case in almond, where Late bloom (Lb) is dominant (Ballester et al, 2001), and in Japanese plum and apricot F 1 populations from low CR cultivars (Campoy et al, 2011;Salazar et al, 2016;Kitamura et al, 2018). However, transgressive segregation toward both early and late blooming was observed in peach F 2 populations (Fan et al, 2010;Bielenberg et al, 2015).…”
Section: Discussionmentioning
confidence: 64%